Variedade relacionada regional e a produtividade das empresas no Brasil - Comparini, Anaisa (2019)
There is a discussion in the literature about the benefits that the regional diversity can result in the companies' productivity due to knowledge recombination, which allows greater opportunities to imitate, share and recombine ideas. However, few studies have been conducted in developing economies. This study aims to analyze the effects of the regional related variety (an indicator that captures the complementarity between sectors) on the companies' productivity. Also, we intend to verify whether the absorptive capacity is a significant moderator in this process and its thresholds. For the empirical study, a database containing data on 80 Brazilian municipalities and 194 companies was used, with data between 2010 and 2014. By calculating the related variety indicator to measure regional diversity and threshold regressions to measure absorptive capacity, this research contributes to the literature, given that empirical studies on this subject in Brazil are still limited. Besides, as the country has a diversified economy, we believe in recombination as an option for economic growth. The results indicate that the related variety has no significant effect on productivity when analyzed alone, but when moderated by the absorptive capacity it has a positive effect.